Exploring The Lexical and Contextual Meaning of The Word “Zauj” in Quranic Discourse - Iqbal Fathi Izzudin; Muhammad Lukman Arifianto; Zulfa Azalia Mujahidah; Moh. Fery Fauzi (Universitas Negeri Malang, 2023)
Qur'an is the holy book of Muslims that contains religious teachings and serves as a guide to the life of all Muslims who demand to be studied and understood. One way to understand the meaning of the verse of the Qur'an is to study it from the point of view of semantics, especially the lexical and contextual meaning of the words that compose the verse. One of the words that is important to study its meaning is the word